Amorphous nickel sulfide nanosheets with embedded vanadium oxide nanocrystals on nickel foam for efficient electrochemical water oxidation. Issue 17 (9th April 2019) - Niu, Yanli; Li, Wei; Wu, Xiuju; Feng, Bomin; Yu, Yanan; Hu, Weihua; Li, Chang Ming
Abstract : A self-supported hierarchical OER catalyst comprising VO/VO2 nanocrystals embedded in amorphous Ni3 S2 nanosheets on Ni foam is reported. Abstract : The development of noble-metal-free active oxygen evolution reaction (OER) catalysts for efficient water electrolysis is in high demand. In this work a novel self-supported hierarchical OER catalyst comprising vanadium oxide (VO/VO2 ) nanocrystals embedded in amorphous trinickel disulfide (Ni3 S2 ) nanosheets grown on Ni foam (VO x /Ni3 S2 @NF, 2 > x > 1) is reported. This VO x /Ni3 S2 @NF demonstrates excellent OER activity and durability in alkaline media. To achieve an OER current density of 100 mA cm −2, it requires an overpotential of only 358 mV (or 330 mV after 95% iR compensation), which is even much lower than that for commercial RuO2 catalysts (446 mV). Detailed investigation unveils that the excellent OER performance of VO x /Ni3 S2 @NF is tightly associated with its rationally combined chemical composition and hierarchical nanostructure; remarkably, the presence of vanadium oxide nanocrystals in the Ni3 S2 nanosheets boosts the OER activity by strengthening the Ni–O bond. This work opens a new route to the rational synthesis of highly efficient OER electrocatalysts, and may help deepen our understanding of the OER process catalyzed by non-precious metal-based hybrid electrocatalysts.